Effects of Mg doping on structural and optoelectronic properties of p-type semiconductor CuCrO2 thin films. (1st March 2022) - Lin, Shih-Hung; Yeh, Rong-Hwei; Chu, Chen; Yu, Ruei-Sung
Abstract: In this study, CuCrO2 thin films are doped with Mg. In the experiment, the Mg content of CuCr1− x Mg x O2 ( x  = 0, 0.015, 0.035, 0.055, 0.075, and 0.095) is increased gradually from 0.2 at% ( x  = 0.015) to 2.17 at% ( x  = 0.095) for increased carrier concentration and electrical conductivity. The amounts of Cu, Cr, and O in the CuCrO2 thin films diverge from the atomic stoichiometric ratio (Cu/Cr/O ratio = 25:25:50). In particular, the thin films contain less Cu and Cr and more O than this ratio, which is suitable for p-type conduction. The results show that Mg is present in the lattice sites of delafossite CuCrO2 and that Mg doping influences the structural and photoelectric properties. By increasing the amount of Mg, the root-mean-square roughness of the thin films decreases from 23.4 to 16.6 nm. In addition, an appropriate increase of Mg doping in the CuCrO2 thin films yields enhanced transmittance of visible light and enhanced absorption of ultraviolet light (300–400 nm). With the increasing amount of Mg, the band gap of CuCrO2 increases from 3.09 eV (undoped, x  = 0) to 3.12 eV ( x  = 0.095). The experiment shows that replacing Cr 3+ with Mg 2+ effectively increases the concentration of carriers, leading to a 64-fold increase in electrical conductivity from 2.43 × 10 −2 to 1.56 (Ω-cm) −1 . A mechanism based on point defects for electrical conduction of hole carriers is proposed. Mg-doped CuCrO2 is thus a candidate for an optoelectronic semiconductor with desirable properties.